ANALYTICAL ANALYSIS OF STEADY FLOW OF NANOFLUID, VISCOUS DISSIPATION WITH CONVECTIVE BOUNDARY CONDITION - Rehman, Ali; Jan, Rashid; Elamin, Abd Elmotaleb A. M. A.; Abdel-Khalek, Sayed; İnç, Mustafa (Vinca Inst Nuclear Sci, 2022)
We focused on the analytical analysis of steady flow of nanofluid, viscous dissipation with convective boundary condition in this work. The MWCNT and SWCNT are used to described the nanofluid. A similarity transformation is applied to convert nonlinear PDE from their dimensional form to dimensionless nonlinear ODE. The developed nonlinear ODE for velocity and temperature profiles are solved by using an approximate analytical technique called the homotopy asymptotic method. Graphs are used to discuss and illustrate the results. Graphs are used to interpret the effects of several factors. Finally, the skin friction and Nusselt number are illustrated in the form of table.
Keywords: MHD (SWCNT, MWCNT); stretching surface; viscous dissipation; homotopy asymptotic method